Implementation of Regional Regulation Number 7 of 2018 concerning Guidelines for Management of Regional Property - Arnan, Dodi; Putri, Rianda Prima; Saufi, Roselina Ahmad (STIA Adabiah, 2023)
This research aims to find out and understand the implementation of Regional Regulation Number 7 of 2018 concerning Guidelines for Management of Regional Property at the Regional Secretariat of South Solok Regency. The type of research carried out was descriptive-qualitative. Informants are determined using purposive techniques. Researchers select informants according to certain predetermined criteria. Data collection techniques in this research used observation, interviews, and documentation studies. The data analysis technique in this research was carried out using four data analysis steps, namely data collection, data reduction, data presentation, and drawing conclusions. Based on the description of the results and research, it can be concluded that regional asset management must be carried out optimally by paying attention to the principles of efficiency, effectiveness, transparency, and public accountability. Implementation of Regional Regulation Number 7 of 2018 concerning Guidelines for Management of Regional Property in South Solok Regency faces a number of obstacles, especially in terms of communication and availability of resources. Lack of communication can hinder coordination between agencies, while limited resources, including facilities and infrastructure, can reduce the effectiveness of asset management. In an effort to overcome obstacles to implementing Regional Regulation Number 7 of 2018 concerning the management of regional property, the Regional Secretariat of South Solok Regency has taken strategic steps. Among them is increasing the frequency and effectiveness of communication through regular meetings between units and clarifying the flow of communication. Other efforts made include optimizing resources by considering additional recruitment, providing relevant training for staff, and investing in technology to support regional asset management.